Survival benefit needed to undergo chemotherapy: Patient and physician preferences. Issue 15 (21st March 2017) - Vaz‐Luis, Ines; O'Neill, Anne; Sepucha, Karen; Miller, Kathy D.; Baker, Emily; Dang, Chau T.; Northfelt, Donald W.; Winer, Eric P.; Sledge, George W.; Schneider, Bryan; Partridge, Ann H.
Abstract : BACKGROUND: Published studies have suggested that most patients with early stage breast cancer are willing, for modest survival benefits, to receive 6 months of adjuvant cyclophosphamide, methotrexate, and 5‐fluorouracil, an older regimen that is used infrequently today. We examined preferences regarding the survival benefit needed to justify 6 months of a contemporary chemotherapy regimen. METHODS: The Eastern Cooperative Oncology Group Protocol 5103 was a phase 3 trial that randomized breast cancer patients to receive standard adjuvant doxorubicin, cyclophosphamide, and paclitaxel with either bevacizumab or placebo. Serial surveys to assess quality of life were administered to patients enrolled between January 1, 2010, and June 8, 2010. Survival benefit needed to justify 6 months of chemotherapy by patients was collected at the 18‐month assessment. A parallel survey was sent to physicians who had enrolled patients in the study. RESULTS: Of 519 patients who had not withdrawn at a time point earlier than 18 months, 87.8% responded to this survey. A total of 175 physicians participated. We found considerable variation in patient preferences, particularly for modest survival benefits: for 2 months of benefit, 57% would consider 6 months of chemotherapy, whereas 96% of patients would consider 6 months of chemotherapy for 24 months. Race and education were associated with the choices. Physicians who responded were less likely to accept chemotherapy for modest benefit. CONCLUSIONS: Among patients who received contemporary adjuvant chemotherapy in a randomized controlled trial, we found substantial variation in preferences regarding benefits that justified undergoing chemotherapy. Differences between patients' and physicians' choices were also apparent. Eliciting preferences regarding risks and benefits of adjuvant chemotherapy is critical. Cancer 2017;123:2821–28. © 2017 American Cancer Society . Abstract : Among patients who receive contemporary adjuvant chemotherapy, there is substantial variation in preferences regarding survival benefit worth undergoing adjuvant chemotherapy. Engaging patients, preferences regarding risks/benefits of treatment is critical in patient‐centered medical decision making and care.